2006
DOI: 10.1086/508436
|View full text |Cite
|
Sign up to set email alerts
|

Sponsorship-Linked Marketing: The Role of Articulation in Memory

Abstract: Corporate sponsorship of events contributes significantly to marketing aims, including brand awareness as measured by recall and recognition of sponsor-event pairings. Unfortunately, resultant advantages accrue disproportionately to brands having a natural or congruent fit with the available sponsorship properties. In three cued-recall experiments, the effect of articulation of sponsorship fit on memory for sponsor-event pairings is examined. While congruent sponsors have a natural memory advantage, results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
193
3
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(213 citation statements)
references
References 16 publications
4
193
3
13
Order By: Relevance
“…Furthermore, in cases where natural fit is low, explanations of fit have been shown to enhance sponsorship effects (Cornwell et al, 2006;Olson and Thjømøe, 2011;Simmons and Becker-Olsen, 2006), while higher interest and expertise in the sponsored event has been shown to enhance the ability of audience members to see fit (Roy and Cornwell, 2004) and enhance overall sponsorship effects (Olson, 2010).…”
Section: Study 1: Comparing Tv Billboards To Tv Advertisingmentioning
confidence: 99%
“…Furthermore, in cases where natural fit is low, explanations of fit have been shown to enhance sponsorship effects (Cornwell et al, 2006;Olson and Thjømøe, 2011;Simmons and Becker-Olsen, 2006), while higher interest and expertise in the sponsored event has been shown to enhance the ability of audience members to see fit (Roy and Cornwell, 2004) and enhance overall sponsorship effects (Olson, 2010).…”
Section: Study 1: Comparing Tv Billboards To Tv Advertisingmentioning
confidence: 99%
“…The desire and pleasure shown by informants only focus on TV show discourse, not at all related to brand, or even product. This phenomenon seems to less support the thesis of La Ferle & Edwards (2006) and Cornwell, et al, (2006) which states that brand placement and program sponsorship give significant consciousness and articulation in the consumer memory. Is this caused by TV show discourse which is not congruent with the functional brand benefit?…”
Section: The Desire and Pleasure Of The Viewers' Successmentioning
confidence: 61%
“…Deery (2004) suggests some intercourse styles of brand (advertising) and entertainment in the form of reality show as follows: the commodification of reality and experience of consumers (where the consumer's brand-related experience becomes a reality show), the commodification of the view (in which objects in reality show are allowed/ recommended to further reveal themselves so that it becomes voyeuristic pleasure for viewers), and the product placement (placement of product/ brand on a reality show). La Ferle & Edwards (2006) claims that product placement makes the appearance of brand in a program (show) is significant to create awareness and image of a brand, especially if the value of the brand is congruent with the program it sponsors, since synergistic sponsorship will provide important articulation in consumer memory (Cornwell, et al, 2006).…”
Section: The Psychoanalysis Of Branded Reality Showmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have therefore examined the factors that encourage unaided and aided recall of the sponsors' brands (e.g., Walliser, 1996). Several authors have shown that an increase in congruence between the sponsor and the sponsored entity improves unaided and aided awareness of the former (e.g., Cornwell et al, 2006;Grohs, Wagner and Vsetecka, 2004;Quester and Farrelly, 1998;Rodgers, 2004). Congruence can be defined as the perceived fit between the sponsor and the event sponsored (Speed and Thompson, 2000).…”
mentioning
confidence: 99%